Sarcopenia in end-stage lung disease patients: a systematic review and meta-analysis - Sheng, Li; Gu, Peipei; Cai, Lingyun; Zhu, Yan; Dong, Meijun; Zeng, Fei (Frontiers in Medicine, 2025)
Sarcopenia is usually an age-related disease in the elderly, which also affects patients with end-stage lung disease (ELD), such as chronic obstructive pulmonary disease, interstitial lung disease, and pulmonary hypertension, significantly affects disease progression and clinical outcomes. Currently, there are various methods for quantifying sarcopenia through muscle mass assessment. This study aimed to evaluate the prevalence of sarcopenia in patients with end-stage lung diseases using meta-analysis and to explore its influencing factors and clinical implications. A systematic search was conducted in English databases, including PubMed, Web of Science (WOS), Embase, Cochrane Library, CINAHL, and Scopus. Two researchers independently assessed study quality using the JBI Critical Appraisal Checklist for Analytical Cross Sectional Studies. Data analysis was performed using Stata 18.0 and R 4.4.3 software. The pooled prevalence of sarcopenia in ELD patients was calculated using a random-effects model, with subgroup analyses to identify sources of heterogeneity. Twenty-four cross-sectional studies involving 6,800 patients were included. The pooled prevalence of sarcopenia in ELD patients was 31.6% (95% CI: 26.5–36.8%). Subgroup analyses revealed higher sarcopenia prevalence in patients aged ≥70 years (vs. <70 years), males (vs. Females), those diagnosed using AWGS2019 criteria (vs.other criteria), dual-energy X-ray absorptiometry (DXA; vs. bioelectrical impedance analysis [BIA]), Asian populations (vs. European/North American populations), and COPD patients (vs. IPF/ILD patients). Sarcopenia is prevalent among patients with ELD, with its prevalence varying across different populations due to multiple influencing factors, resulting in distinct clinical outcomes. It is recommended to implement targeted intervention strategies based on these factors to reduce the incidence of sarcopenia and enhance the quality of life.Systematic review registrationIdentifier, CRD420251028682 (PROSPERO).